Prevalence and associated factors of chronic kidney disease among adults receiving antiretroviral therapy at Hawassa University Comprehensive Specialized Hospital - Yitayew Ewnetu Mohammed; Desalegn Dawit Assele; Sinetibeb Tadesse Amsalu; Yared Habtie Tayachew; Teshome Abuka; Menbere Weldecherkos; Ashagrachew Haile; Sileshi Demelash (PLoS ONE, 2025)
Background Antiretroviral therapy (ART) improves life expectancy in people living with human immunodeficiency virus (HIV). The risk of chronic kidney disease (CKD) is greater in people living with HIV (PLWH) than in the general population, and it is becoming a significant public health issue, increasing disease progression and complicating treatment. However, patients in Africa are not routinely screened due to resource constraints, which leads to a high CKD burden. Identifying the predisposing factors is the crux of mitigating the burden of CKD. We investigate the prevalence of chronic kidney disease and associated factors among PLWH at the Hawassa University Comprehensive Specialized Hospital (HUCSH). Methods A cross-sectional study was conducted from August 2 to September 3, 2022, at the HUCSH ART clinic, in Hawassa, Ethiopia. Data were collected from 338 PLWH through interview and medical record review. Renal function was assessed using the estimated glomerular filtration rate (eGFR) calculated using the “Chronic Kidney Disease Epidemiology Collaboration” (CKD-EPI) formula. Data were entered in Epidata version 3.01 and analyzed using Statistical Package for the Social Sciences (SPSS) version 26.0. Both bivariable and multivariable logistic regression analyses were used to identify factors associated with CKD among PLWH. An adjusted odds ratio (AOR) with a 95% Confidence Interval (CI) was reported to show the strength of the association. The goodness of fit of the model was checked by the Hosmer and Lemeshow test. The statistical significance of associations was declared at a p-value < 0.05. Results The study included 338 PLWH with a response rate of 96%. The mean (standard deviation (SD) age of the participants was 44.4 ( ± 10.9) years. The female-to-male ratio was 1:1.8. The prevalence of CKD was 7.7% [95% CI: 5–10.7%]. History of alcohol use [AOR: 5.4; 95%CI: 1.32, 21.7], having chronic medical illness [AOR: 5.3; 95%CI: 1.45, 19.1], late stage of HIV [AOR: 5.2; 95%CI: 1.1, 25.3], opportunistic infections [AOR: 5.4; 95%CI: 1.25, 23.4], and low baseline hemoglobin level [AOR: 7.9; 95%CI: 2.58, 24.4] were significantly associated with CKD. Conclusion The study found that CKD prevalence in PLWH was high. Factors associated with CKD include alcohol use, chronic medical illness, advanced WHO HIV stage, opportunistic infections, and low hemoglobin. Therefore, PLWH should be regularly screened for early diagnosis and management of CKD, and those with associated factors should be closely monitored.